The plastid‐localized lipoamide dehydrogenase 1 is crucial for redox homeostasis, tolerance to arsenic stress and fatty acid biosynthesis in rice - Chen, Ting‐Ting; Zhao, Peng; Wang, Yuan; Wang, Han‐Qing; Tang, Zhu; Hu, Han; Liu, Yu; Xu, Ji‐Ming; Mao, Chuan‐Zao; Zhao, Fang‐Jie; Wu, Zhong‐Chang (The New phytologist, 2024)
Summary Soil contamination with arsenic (As) can cause phytotoxicity and reduce crop yield. The mechanisms of As toxicity and tolerance are not fully understood. In this study, we used a forward genetics approach to isolate a rice mutant, ahs1, that exhibits hypersensitivity to both arsenate and arsenite. Through genomic resequencing and complementation tests, we identified OsLPD1 as the causal gene, which encodes a putative lipoamide dehydrogenase. OsLPD1 was expressed in the outer cell layer of roots, root meristem cells, and in the mesophyll and vascular tissues of leaves. Subcellular localization and immunoblot analysis demonstrated that OsLPD1 is localized in the stroma of plastids. In vitro assays showed that OsLPD1 exhibited lipoamide dehydrogenase (LPD) activity, which was strongly inhibited by arsenite, but not by arsenate. The ahs1 and OsLPD1 knockout mutants exhibited significantly reduced NADH/NAD+ and GSH/GSSG ratios, along with increased levels of reactive oxygen species and greater oxidative stress in the roots compared with wild‐type (WT) plants under As treatment. Additionally, loss‐of‐function of OsLPD1 also resulted in decreased fatty acid concentrations in rice grain. Taken together, our finding reveals that OsLPD1 plays an important role for maintaining redox homeostasis, conferring tolerance to arsenic stress, and regulating fatty acid biosynthesis in rice.